Laboratory study on stilling basin as an integral part of energy dissipator system - Nik Fatin, Nik Mohamed (2010)
Water flow from upstream to downstream will create to high energy at the time when it reaches the downstream. This situation will cause damage or critical erosion at spillways toe, weir bed and downstream of river. In order to overcome this problem, the water flow velocity has to be reduced. The solution for this problem is by constructing an energy dissipating structure at the effected areas. In this study, baffles were used as the experimental energy dissipating structure. Various size and arrangement of baffles at the downstream of the model were tested to determine the most effective result in reducing the water flow velocity. The relationship between the percentage of velocity decrease and the spacing between the baffles were determined by plotting graphs. The decreases in velocity depends on the size of baffles and the arrangement of baffles at the stilling basin.